PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN DALAM MENYELEKSI PENERIMAAN SISWA BARU MENGGUNAKAN METODE TOPSIS (STUDI KASUS: SMA NEGERI 02 SENDAWAR) - Yosepinus Trinaldo; Magdalena A. Ineke Pakereng (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
This research aims to design a decision support system that can help schools, especially SMAN 02 Sendawar in accepting new students. The method that will be used to deal with the problems that occur is the TOPSIS method (Technique For Others Preference By Similitary To Ideal Solution). This research was conducted to get the best students in the selection, based on predetermined criteria. The criteria used in this study were test results, report cards, distance, and completeness of the files. The results of the study will provide a list of students who have the highest preference scores, and based on the highest preference scores, students will be accepted by the school.